2013
DOI: 10.1002/etc.2365
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating toxicological interaction of single‐walled carbon nanotubes with dissolved metals

Abstract: The present study explored the ecotoxicology of single-walled carbon nanotubes (SWCNTs) and their likely interaction with dissolved metals, with a focus on the effect of in vivo exposure in marine mussels. Any nano-scale effects were negated by the tendency of uncoated SWCNTs to agglomerate in water, particularly with high ionic strength as is the case in estuarine and full-strength seawater. However, SWCNTs, in combination with natural organic matter, remained suspended in seawater for long enough to become a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In conclusion, the above experiments demonstrated a possible antibacterial process of SWCNTs on S. aureus cells: SWCNTs maybe caused cell wall breakage, and then internalized into the bacteria cell. Ag-NPs internalized into S. aureus cells and caused DNA damage [17,[18][19][20][21]. SWNTs can exhibit strong antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the above experiments demonstrated a possible antibacterial process of SWCNTs on S. aureus cells: SWCNTs maybe caused cell wall breakage, and then internalized into the bacteria cell. Ag-NPs internalized into S. aureus cells and caused DNA damage [17,[18][19][20][21]. SWNTs can exhibit strong antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Hemocytes and gill cells were analyzed for genotoxicity using the comet assay. The single‐cell gel electrophoresis or comet assay was performed according to Singh and Hartl (2012) and Al‐Shaeri et al (2013). A detailed description of the methodology can be found in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The ENMs are often functionalized for improved performance, which will also confer a new identity on the material, potentially leading to distinct environmental fate, behavior, and biological effects compared with the core ENM (Perreault et al, 2014). For that reason, and because of the ability of mussels to sort particulates (Al‐Shaeri et al, 2013), we used CuO and TiO 2 ENMs with a series of functionalizations (carboxyl [COOH], polyethylene glycol [PEG], and ammonia [NH 3 ]) to investigate whether distinct hazards and fate are dictated and/or can be controlled by functionalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies reported the ability of carbon nanotubes to adsorb heavy metal ions but few investigated the effect of this property on the organisms potentially exposed (Li et al 2004, Li et al 2005, Lu et al 2006). A previous study described a potentiating toxicological effect of SWCNT, suspended with organic matter in seawater, co-exposed with divalent metals at very low concentration (µg/L range) on DNA integrity of the mussel Mytilus edulis (Al-Shaeri et al 2013). In other studies, lead toxicity to a freshwater fish increased in the presence of purified MWCNT (Martinez et al 2013) while, in contrast, SWCNT in sediments significantly reduced bioaccumulation of hydrophobic carbon to the deposit/suspensionfeeding of a polychaete (Ferguson et al 2008).…”
Section: Introductionmentioning
confidence: 94%